The Rushdiah Club: Its roles in Malay Societies, 1892-1940 - Oktasari, Wiwin; Zakariya, Hafiz (IIUM Press, International Islamic University Malaysia, 2017)
This study examines the emergence, growth and impact of The Rushdiah Club in Malay Societies. It utilizes a historical methodology in answering the key research questions. This study traces the enigmatic literati-publisher of Riau-Lingga Sultanate, Rushdiah Club, and their roles in cultural transformation of Malay Societies. Starting by a discussion on the socio-political background, the rapid growth of Islam and writing culture in the end of 19th century Riau Lingga, this study also follows the developments of Rushdiah Club’s writing and printing activities in the ensuing century, the expansion of their printing practices to Singapore and Penang